Seismic Ground Response Analysis of Input Earthquake Motion and Site Amplification Factor at KUET - Akter, Sonia (Journal of the Civil Engineering Forum, 2021)
Ground motion is the movement of the earth’s surface due to explosions or the propagation of seismic waves. In the seismic design process, ground response analysis evaluates the impact of local soil conditions during earthquake shaking. However, it is difficult to determine the dynamic site response of soil deposits in earthquake hazard-prone areas. Structural damage has a great influence on the selection of input ground motion, and in this study, the importance of bedrock motion upon the response of soil is highlighted. The specific site response analysis is assessed through “DEEPSOIl" software with an equivalent linear analysis method. Furthermore, four input motions including Kobe, LomaGilroy, Northridge, and Chi-Chi were selected to obtain normalized response spectra. This study aims to obtain the site amplification of ground motion, peak spectral acceleration (PSA), and maximum peak ground acceleration (PGA) based on shear wave velocity from the detailed site-specific analysis of Bangabandhu Sheikh Mujibor Rahman hall at Khulna University of Engineering & Technology. The maximum shear wave velocity obtained was 205 m/s while the amplification factor varied from 4.01 (Kobe) to 1.8 (Northridge) for rigid bedrock properties. Furthermore, the Kobe earthquake produced the highest (4.3g) PSA and the Northridge earthquake produced the lowest (1.08g) PSA for bedrock, with Vs=205 m/s. The surface PGA values were acquired in the range of 0.254g (Northridge) to 0.722g (Kobe), and the maximum strain values for Kobe earthquakes were in the range of 0.016 to .303. Therefore, the surface acceleration values were very high (>0.12g) for the Kobe earthquake motion.